The Global Seismic Moment Rate of Mars After Event S1222a - M. Knapmeyer; S. Stähler; A.‐C. Plesa; S. Ceylan; C. Charalambous; J. Clinton; N. Dahmen; C. Durán; A. Horleston; T. Kawamura; D. Kim; J. Li; et al. (Geophysical Research Letters)
Abstract The seismic activity of a planet can be described by the corner magnitude, events larger than which are extremely unlikely, and the seismic moment rate, the long‐term average of annual seismic moment release. Marsquake S1222a proves large enough to be representative of the global activity of Mars and places observational constraints on the moment rate. The magnitude‐frequency distribution of relevant Marsquakes indicates a b‐value of 1.06. The moment rate is likely between 1.55×1015Nm/a and 1.97×1018Nm/a, with a marginal distribution peaking at 4.9×1016Nm/a. Comparing this with pre‐InSight estimations shows that these tended to overestimate the moment rate, and that 30% or more of the tectonic deformation may occur silently, whereas the seismicity is probably restricted to localized centers rather than spread over the entire planet.